2018
DOI: 10.1038/s41419-018-0683-x
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 exacerbates tumor growth through regulating the cell cycle and accelerates migration/invasion via targeting miR-221/222 in cervical cancer

Abstract: High-mobility group AT-hook1 (HMGA1, formerly HMG-I/Y), an architectural transcription factor, participates in a number of tumor biological processes. However, its effect on cervical cancer remains largely indistinct. In this study, we found that HMGA1 was generally overexpressed in cervical cancer tissues and was positively correlated with lymph node metastasis and advanced clinical stage. Via exogenously increasing or decreasing the expression of HMGA1, we showed that HMGA1 affected the proliferation, colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 74 publications
3
54
0
1
Order By: Relevance
“…The HMGA1 protein is a structural factor that binds to DNA regions rich in adenine-thymine (A-T), which have no intrinsic transcriptional activity 16 . HMGA1 drives gene transcription by promoting the assembly and stability of higher transcriptional complexes 18 . Previous studies demonstrated that HMGA1 deficiency induces cardiac hypertrophy 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HMGA1 protein is a structural factor that binds to DNA regions rich in adenine-thymine (A-T), which have no intrinsic transcriptional activity 16 . HMGA1 drives gene transcription by promoting the assembly and stability of higher transcriptional complexes 18 . Previous studies demonstrated that HMGA1 deficiency induces cardiac hypertrophy 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…High-mobility family AT-Hook1 (HMGA1) binds to the AT-rich region of DNA 13 . HMGA1 takes part in various fundamental processes at the molecular and cellular level, such as cell cycle progression 14 , embryologic development 15 , neoplastic transformation 16 , differentiation 17 , apoptotic cellular metabolism, and DNA repair 18 . Research has uncovered that cardiac hypertrophy and myelo-lymphoproliferative disorders were observed in mice with HMGA1 haploinsufficiency 19 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, HMGA1 can promote breast cancer angiogenesis via supporting the transcriptional activity of FOXM1 [29]. HMGA1 exacerbates cervical cancer growth via regulating cell cycle and migration/invasion capacity through targeting miR-221/222 [30]. HMGA1 is correlated with breast cancer malignant status [31].…”
Section: Discussionmentioning
confidence: 99%
“…e abnormal high expression of miR-221/222 is involved in various cancers (Table 1), which promotes the malignant proliferation, immune escape, invasion, and metastasis of tumor cells [94]. rough the retrieval and statistics of the databases (including PubMed and Web of Science), the oncogene upregulated with overexpression of miR-221/222, including glioblastoma [31], gastric cancer [32,33], bladder cancer [35], hepatocellular carcinoma [38,39,51,59], lung cancer [36,37], liver cancer [29,51], breast cancer [60][61][62][63], cervical cancer [64,68,95], ovarian cancer [66,69,70], endometrial carcinoma [74], melanoma [75,76], pancreatic cancer [77], thyroid cancer [78,79], multiple myeloma [80], chronic lymphocytic leukemia [79], oral carcinoma [82], retinoblastoma [83,96], nasopharyngeal carcinoma [84], and prostate carcinoma [85], was summarized. However, the upregulation of miR-221/222, also referred to as tumor suppressor miRNA, targeting overexpress oncogenes, leads to tumor suppressions.…”
Section: Mir-221/222's Targets and Molecular Modulationmentioning
confidence: 99%
“…High-mobility group AT-hook1 (HMGA1, formerly HMG-I/Y), an architectural transcription factor, participates in a number of tumor biological processes. Fu et al [68] have shown that HMGA1 is highly expressed in CSCC tissue, which promotes the migration and invasion of cervical cancer cells and showed that the mechanism of HMGA1 cancer promotion is targeting the promoter region of miR-221/222 to enhance the expression of miR-221/222. Among them, miR-221/222 targeted on the 3′UTR of tissue inhibitor of metalloproteinases 3 (TIMP3), while TIMP3 downregulated and MMP2/MMP9 upregulated, and miR-221/222-TIMP3-MMP2/MMP9 axis participates in the migration and invasion process ( Figure 5).…”
Section: Role Of Mir-221/222 In Cervical Cancermentioning
confidence: 99%